Faktor-Faktor Yang Mempengaruhi Tidak Terpenuhinya Pilar 4 Dan Pilar 5 Di Wilayah Kerja Puskesmas Campalangian Kecamatan Campalangian Kabupaten Polewali Mandar - Sulasmi, Sulasmi; Suciani, Umrah Nur; Haderiah, Haderiah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Community Led Total Sanitation or CLTS is an approach to changing hygiene and sanitation behavior through the triggering method. Sanitation is still a household problem that will have direct or indirect impacts on health and the environment in an area. This study aims to determine the factors that influence the non-fulfillment of CLTS pillar 4 and pillar 5 in the working area of the Campalagian Health Center, Kec. Campalagian, Kab. Polewali Mandar. This type of research is analytic observational with a cross sectional approach, and uses a sample of 80 households with a sampling method that uses Simple Random Sampling. For data processing using the chi-square statistical test with the help of computer software. The results showed that there was an effect of not fulfilling CLTS Pillar 4 and Pillar 5 ehich included environmental factors, human, resources, and regulations. Based on the statistical test result for environmental factors, namely pilllar 4 the result were p = 0.003, and pillar 5 was p = 0.004, while for the human resource factor, namely pillar 4 the fresult were obtained p = 0,000 and pillar 5 p = 0.004 and for regulatory factors that is on pillar 4 the value of p = 0.004 is obtained, and pillar 5 p = 0.002. This is because most people think that the facilities for garbage disposal and the management of household liquid waste are not important enough to have. The conclusion of this study is that there is an influence between environmental factors, human resources, and regulations on the non-fulfillment of CLTS pillars 4 and pillar 5. So that the community is advised to be able to implement the of CLTS Pillar 4 program such as providing waste disposal facilities and Pillar 5 such as making SPAL (canal waste water disposal) in accordance with health requirements. Keywords : CLTS Pilar 4 dan 5; Enviroment; Resources People and Regulation